Form of Conservation and Spatial Planning of House Betang, Suku Dayak Central Kalimantan - Agung Gde Djaja Bharuna S, Anak Agung Gde Djaja; Ketut Acwin Dwijendra, Ngakan (ASTONJADRO, 2022)
The development of the Betang house of the Dayak tribe in Central Kalimantan from a long house model inhabited by several families into a private house with a much changed shape and spatial pattern. Factors that cause changes that occur in general, include: changes in residents' needs; Changes in local customs and traditions, with the loss of gathering habits such as traditional feasts and tiwah rituals; and changes in the form of building elements, both in form and in the materials used. Changes in the form of houses and spatial patterns that occur are caused by changes in the functions and demands of residents as well as cultural acculturation. There needs to be conservation efforts as a tangible form of conservation in this Betang house to preserve the shape of the Betang house as before.